Analysis of Action of Madhutailika Vasti in Vatarakta Through its Contents - Unnimaya G M; T K Sujan; Ambili Krishna (International Journal of Ayurveda and Pharma Research, 2021)
Vatarakta is a Vatapradhana tridoshaja vyadhi signifies the association of Vata along with Pitta and Rakta dhatu getting Sthanasamshraya at Kaphasthana. It is a Vyadhi of Madhyama rogamarga with Asthi, Sandhi, Upadhatu’s like Peshi, Snayu and Sira as target sites. With the greater affection of Dhatwagni at different level, the Samprapti of the disease progresses to multisystem involvement. This lights the fact that the sites of affection are deep and Bala of the Rogi is highly diminished in Vatarakta. So, a treatment which is capable of dislodging the deep seated Doshas and bringing Bala to the Rogi is found to be appropriate. Vasti, by its Srotosodhana, Vatanulomana and Brumhana property achieves both the goals. Vasti cures the disease of all Doshas of all the three Margas namely Sakha, Koshta, and Marmasthi sandhi and it completely destroys the vitiated Vata dosha by entering in to its Moolasthana. Different types of Vastis can be used in Vatarakta and it is found to be very effective. When the Bala of Vatarakta patients are taken in to consideration, a Vasti which is Brumhana, Vatashamana, Rakta prasadana and Rasayana is more appropriate. Madhutailika vasti is Snigdha, Mridu, and Nirapaaya satisfies the selection criteria. The aim of this paper is to demonstrate the mode of action of Madhutailika vasti with Madhuyashtyadi taila in Vatarakta by critically analysing the pharmacological properties.